Hak Pekerja Terkena Phk Sebelum Masa Kerja Berakhir - Aziz Ramadhani, Muhamad Abdul; Shidqi, Valevi Nur (Peneliti.net, 2025)
A painting agreement must conclude once its designated duration has been fulfilled. Nonetheless, it is frequently observed that the contract may terminate prior to the agreed-upon timeline, despite explicit provisions. This study aims to ascertain the rights of employees who are dismissed before the completion of the contract period and to identify the legal remedies that can be pursued. The research employs a normative legal approach utilizing statutory analysis. The results indicate that employees are entitled to receive compensation for the remainder of the contract duration if the employer unilaterally ends the employment before the contract expires, as outlined in Article 62 of the Employment Law. Additionally, the findings suggest that no individual efforts have been made to address this situation, with the final option being based on SEMA. Ultimately, judicial decisions must ensure that employees receive their entitlements for the remaining contract period in accordance with Article 62 of the Labor Act